2020
DOI: 10.3390/ijerph17239118
|View full text |Cite
|
Sign up to set email alerts
|

The Recovery Benefit on Skin Blood Flow Using Vibrating Foam Rollers for Postexercise Muscle Fatigue in Runners

Abstract: Purpose: To determine the effect of vibrating rollers on skin blood flow after running for recovery from muscle fatigue. Method: 23 healthy runners, aged between 20 to 45 years, participated in a crossover trial. Muscle fatigue was induced by running, and recovery using a vibrating roller was determined before and after the intervention. Each subject was measured at three time points (prerun, postrun, and postroller) to compare skin blood flow perfusion and blood flow oscillation at the midpoint of the dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 36 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…The main characteristics of the 10 studies included in this systematic review are shown in Table 1 . Jointly, they evaluated a total of 236 subjects (74.1% male) through a crossover design ( n = 7) [ 9 , 13 , 14 , 19 , 29 31 ] or a randomized trial ( n = 3) [ 10 , 15 , 18 ]. Seven investigations [ 9 , 10 , 13 15 , 29 , 31 ] compared the use of VFR with FR and other studies analyzed the effects of VFR in comparison with static ( n = 4) [ 14 , 19 , 27 , 28 ] or dynamic stretching ( n = 3) [ 15 , 19 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The main characteristics of the 10 studies included in this systematic review are shown in Table 1 . Jointly, they evaluated a total of 236 subjects (74.1% male) through a crossover design ( n = 7) [ 9 , 13 , 14 , 19 , 29 31 ] or a randomized trial ( n = 3) [ 10 , 15 , 18 ]. Seven investigations [ 9 , 10 , 13 15 , 29 , 31 ] compared the use of VFR with FR and other studies analyzed the effects of VFR in comparison with static ( n = 4) [ 14 , 19 , 27 , 28 ] or dynamic stretching ( n = 3) [ 15 , 19 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, vibration has been added to the FR devices with the aim of increasing their benefits [ 8 ]. Specifically, this vibration was expected to produce an in-depth stimulation of the tissues rolled, especially the mechanoreceptors of the joints and blood vessels [ 9 , 10 ]. Moreover, a greater contribution of the mechanoreceptors has been reported with vibration foam roller (VFR), suggesting that the vibration could influence deeper into the tissue through mechanisms of the neuromuscular system but also at a central level [ 8 , 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the referenced studies had included results that were based on whole-body vibration and not local vibration. Other previous studies compared the effects of VFRs and FRs in improving blood flow to the skin and reported that although they were more effective, there was no statistically significant difference ( Lai et al, 2020 ). We consider that the pressure of the FR along with vibration worked synergistically to improve the blood flow.…”
Section: Discussionmentioning
confidence: 99%